Modelagem da dinâmica espacial do uso da terra para o município de São Carlos : condições pretéritas e futuras - Stanganini, Fábio Noel (2016)
Urban area growth intensification process of São Carlos’s county has been quickly rising over the years and without helpful elements on planning and management of these areas, leading changes on spatial dynamic, and significant changes on environmental conditioning and consequently in natural landscape. This work aims an historical and temporal construction of land’s use and occupation through an analysis during a period of 30 years by means of LANDSAT satellite images 4, 5, 7 e 8 with the sensors MMS, TM, TM+ e OLI, concomitantly was build through these analysis a little perspective of future sceneries for the years of 2020 and 2030 through the DINAMICA EGO’s software, totalizing a period of 50 years of study about urban area growth process. The tesis, based on obtained data of 1980, 1990, 2000 e 2010, had demonstrated the area situation on this time period and immediate surroundings of the city regarding land’s use and occupation, divided in 5 classes of use, being them, exposed soil, agricultural area, vegetation, urban area and hydrography, by means of informations’ classification and visual interpretation. Were developed thematic cards that will help on the provided scenarios build and the future frames in a little period of time. The results point out that, like the population rises, vehicles rise and consequently generating environmental’s degradation and impacts almost irreversible due to intense occupation form. Another important factor is the pressure above natural resources, especially vegetation and water resources. The historical approach and the modeling process of spatial information with a provided view of future scenarios provides subsidies to understand the land’s use transformation, like the hydrography sub basin’s occupation, floods, urban water drain, lost of vegetation and waterproofing increase, generating this way a technical device for future interventions and decision-making of local public power.